Neurogenic modulation by neurokinin-1 receptor antagonist, cp-96,345 to inhibit rheumatoid arthritis development in adjuvant induced arthritis rat model - Wirasasmita, Yuyun; Rahmadi, Mahardian; Susilo, Imam; Khotib, Junaidi (Folia Medica Indonesiana, 2017)
Rheumatoid arthritis (RA) is a chronic form of persistent inflammation. Meanwhile, Substance P is the most associated neuropeptide in neurogenic inflammation and hyperalgesia commonly found in chronic pain. Substance P act by binding to neurokinin-1 receptor. The present study was conducted to evaluate the effect of neurokinin-1 receptor antagonist (CP-96,345) on Adjuvant Induced Arthritis rat model, induced by Complete Freund's Adjuvant (CFA). The objective is to attenuate neurogenic inflammation which in turn will increase the latency time of hyperalgesia response, decreases neurokinin-1 receptor expression, and inhibits the development of RA in AIA rat model. Rats were intra-articularly injected with CFA 1 hour after the administration of CP-96,345 either by 0.63 µg/gr; 1.25 µg/gr; or 2.5 µg/gr also intra-articularly. Caliper measurements and hot-plate test were performed on day 0, 3, 5, 7, 9, 11, and day 13. Expression of neurokinin-1 receptor in joint tissue were evaluated by immunohistochemistry, and RA progress in joint tissue were observed hystopathologically. CP-96,345 at 2.5 µg/gr significantly increases the latency of hyperalgesia response time on CFA induced rats (p=0.044) and decreased the neurokinin-1 receptor expression in joint tissue (p=0.029) compared to CFA induced rats. There was no significant difference for caliper measurements and RA progress between CFA incduced rats and treated group. Conclusively, CP-96,345 increases the latency of hyperalgesia response time and decreases the NK-1 receptor expression in rat joint but could not inhibit RA progression.